2014
DOI: 10.1620/tjem.233.275
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Five Prevalent Mutations of <i>SLC25A13</i> Gene in Guangdong, China: A Molecular Epidemiologic Survey of Citrin Deficiency

Abstract: Citrin is the liver-type aspartate/glutamate carrier isoform 2 (AGC2) encoded by SLC25A13 gene, playing important roles in the urea cycle and the malate-aspartate shuttle. Citrin deficiency (CD) has proven a disease entity with high prevalence in south China, including Guangdong with the largest population, but CD epidemiology in this province has not been well characterized. This study aims to screen for five prevalent SLC25A13 mutations, c.851_854del (p.R284fs286X), c.1638_1660dup (p.A554fs570X), c.615+5G>A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Although about 200 Chinese NICCD patients have been diagnosed via SLC25A13 analysis to date 22 25 26 27 , this number was rather limited, since China might have 85700 CD patients according to provisional epidemiological data 19 27 28 . Moreover, the SLC25A13 mutations worldwide demonstrate remarkable heterogeneity 12 22 23 24 27 29 30 31 32 33 34 35 36 37 38 . China is a vast country with a huge population, but the SLC25A13 genotypic features of CD patients, including the mutation spectrum and their geographic distribution, remains far from being well clarified in our country.…”
mentioning
confidence: 99%
“…Although about 200 Chinese NICCD patients have been diagnosed via SLC25A13 analysis to date 22 25 26 27 , this number was rather limited, since China might have 85700 CD patients according to provisional epidemiological data 19 27 28 . Moreover, the SLC25A13 mutations worldwide demonstrate remarkable heterogeneity 12 22 23 24 27 29 30 31 32 33 34 35 36 37 38 . China is a vast country with a huge population, but the SLC25A13 genotypic features of CD patients, including the mutation spectrum and their geographic distribution, remains far from being well clarified in our country.…”
mentioning
confidence: 99%
“…A molecular survey on citrin deficiency epidemiology in Guangdong province, China, reported that the carrier rate of the four prevalent SLC25A13 mutations was ~2.06% (50/2,428), theoretically, with the number of citrin-deficiency patients >11,000 in this population ( 15 ). These survey samples were collected from different cities in Guangdong province, but did not include Jiangmen city.…”
Section: Discussionmentioning
confidence: 99%
“…The overall pathogenic variant carrier rate has been reported to be as high as 2% in southern China, which is the highest carrier frequency currently reported ( 13 , 15 ). A total of >11,000 individuals are estimated to be homozygous or compound heterozygous for SLC25A13 pathogenic variants in the Guangdong province in southern China ( 15 ). Currently, >80 SLC25A13 pathogenic variants have been identified, but among them, four prevalent mutations c.851_854del (p.R284fs286X), c.1638_1660dup (p.A554fs570X), IVS6+5G>A (p.A206fs212X), and IVS16ins3kb (p.A584fs585X) account for >80% of the Chinese population who exhibit citrin deficiency ( 16 18 ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…To date, a total of 106 pathogenic SLC25A13 mutations/variations have been reported [ 11 , 14 , 22 , 25 , 32 – 41 ], most of which are point mutations or short insertions/deletions. Among the SLC25A13 mutations detected in Chinese CD patients, c.851_854del, c.1638_1660dup, c.615+5G>A and IVS16ins3kb account for about 85% of all mutated alleles [ 11 , 25 , 36 ]. Nowadays, these four high-frequency mutations have been screened by conventional means of Polymerase Chain Reaction (PCR), Long and Accurate PCR (LA-PCR) and PCR-Restriction Fragment Length Polymorphism (PCR-RFLP) procedures, respectively, as the basic molecular targets for NICCD diagnosis.…”
Section: Introductionmentioning
confidence: 99%